Education for security versus education for sustainable development - Agnieszka Klimska (Forum Pedagogiczne, 2021)
The article presents issues related to the practice of sustainable development against the background of selected strategies and models of education. In the face of the ecological crisis, as well as growing threats to the social and natural environment, the need to modify education for sustainable development programmes appears more apparent. It has been proposed that this model of education should be supported by education for security, since security is a need, value, and a dynamic social process, and any actions in its favour, offer a strong incentive for people to be active and adopt new attitudes.